Gender Equity in Inheritance System: The Collaboration of Islamic and Bugis Luwu Customary Law - Andi Sukmawati Assaad; Saifuddin Zuhri Qudsy; Baso Hasyim; Muhammad Taufan Badollahi; Abdul Wahid Haddade (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
This article is the result of research on the cultural heritage of the Bugis people of Luwu, South Sulawesi. The research questions that were raised were: how is inheritance practiced among the indigenous people of Bugis Luo, what is the meeting point of inheritance between Islamic law and customary law, and how do Islamic law and customary law combine to create gender. Primary data was collected through in-depth and structured interviews, as well as on-site observation. The analysis was performed using interpretive methods. The study was conducted by analyzing the regulations related to the legal issues discussed by analyzing the laws and comparing the decisions of the Luwu and Bugis courts with the perspective of customary law and Islamic law. The analysis used in this study resulted in women and men being equal. Bugis Luwu Sulawesi has a pluralistic hereditary system with both Islamic and traditional elements. Equal rights and rules are general ideas. This research is based on the proposed mixed inheritance model: masssideppungeng that links the heirs to family, government, and religious customary authorities, the distribution of assets to field conditions, and proportionally identifies the needs, wants, and goals of the inheritors.